Superior basal and plastic thermal responses to environmental heterogeneity in invasive exotic stemborer Chilo partellus Swinhoe over indigenous Busseola fusca (Fuller) and Sesamia calamistis Hampson - Mutamiswa, Reyard; Chidawanyika, Frank; Nyamukondiwa, Casper (Wiley, 2022)
Lepidopteran stemborers are the most destructive insect pests of cereal crops in sub-Saharan Africa. In nature, these insects are often exposed to multiple environmental stressors, resulting in potent impact on their thermal tolerance. Such environmental stressors may influence their activity, survival, abundance and biogeography. In the present study, we investigate the effects of acclimation to temperature, starvation and desiccation on thermal tolerance, measured as critical thermal limits [critical thermal minima (CTmin) and maxima (CTmax)] on laboratory-reared economic pest species Chilo partellus Swinhoe (Lepidoptera: Crambidae), Busseola fusca (Fuller) and Sesamia calamistis Hampson (Lepidoptera: Noctuidae) using established protocols. Low temperature acclimation results in improved CTmin for B. fusca and C. partellus, whereas high temperature acclimation enhances the same trait for B. fusca and S. calamistis. Similarly, high temperature and starvation pretreatment improve CTmax for C. partellus relative to S. calamistis and B. fusca. In addition, starvation and desiccation pretreatments improve CTmin for all stemborer species. Furthermore, rapid cold-hardening (RCH) enhancs CTmin for B. fusca and C. partellus, whereas rapid heat-hardening (RHH) improves the same trait for C. partellus. However, RCH and RHH impair CTmax for all stemborer species. These findings show differential thermal tolerances after exposure to heterogeneous environmental stress habitats. Chilo partellus, of exotic origin, shows a higher magnitude of basal thermal tolerance plasticity relative to the indigenous African species S. calamistis and B. fusca. This indicates that C. partellus may have a fitness and survival advantage under climate-induced heterogeneous environments, and also have a greater chance for geographical range expansion and invasion success compared with the indigenous B. fusca and S. calamistis.